2018
DOI: 10.1108/tqm-07-2017-0087
|View full text |Cite
|
Sign up to set email alerts
|

Waiting too long: bottlenecks and improvements – a case study of a surgery department

Abstract: Purpose The purpose of this paper is to promote a business process approach for developing and improving the efficiency of hospital service quality in order to reduce clinical risks and increase patients satisfaction. The problems healthcare facilities face are how to reduce waste and risk and improve quality. The adoption of a process-focused organization could reduce organizational errors which have a negative influence on performance. Design/methodology/approach The research is based on a case study metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Using a sensory marketing (Hultén et al , 2009; Krishna, 2012) approach in their research on patient experience during hospitalization, Ugolini et al (2014) found that the five basic human senses of sight, hearing, smell, taste and touch influence both clinical patient outcomes and their satisfaction from the medical treatment. A five-senses perspective to quality in hospitals (Baldassarre et al , 2018; Groeger, 2012; Ugolini et al , 2014) suggests that the five basic human senses influence patient decision-making processes in hospitals. In this study, the hospital team communication corresponds to human senses of what a patient can hear ; the health-care team action orientation corresponds to what a patient can see ; and the patient hospital room environment corresponds to what a patient can touch, smell and taste during his/her hospital room for the stay for their medical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Using a sensory marketing (Hultén et al , 2009; Krishna, 2012) approach in their research on patient experience during hospitalization, Ugolini et al (2014) found that the five basic human senses of sight, hearing, smell, taste and touch influence both clinical patient outcomes and their satisfaction from the medical treatment. A five-senses perspective to quality in hospitals (Baldassarre et al , 2018; Groeger, 2012; Ugolini et al , 2014) suggests that the five basic human senses influence patient decision-making processes in hospitals. In this study, the hospital team communication corresponds to human senses of what a patient can hear ; the health-care team action orientation corresponds to what a patient can see ; and the patient hospital room environment corresponds to what a patient can touch, smell and taste during his/her hospital room for the stay for their medical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Barnab e and Giorgino (2017) discussed a case study in a healthcare setting about how the lean strategy (Hoshin Kanri) can be operationalised using the X-matrix reporting tool and simulation techniques involving role play. Baldassarre et al (2018) presented a case study of reducing the bottleneck and waiting through process improvements in the surgery department of an Italian hospital. Gijo and Antony (2014) too addressed the issue of longer patient waiting time in the outpatient department (OPD) of a super-speciality hospital in India using the Lean Six Sigma (LSS) methodology.…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate goal is to achieve an improvement routine for each organizational process based on the criteria determined by the hospital's strategy, where the indicators in each area are monitored and in line with the priority set. The new improvement group members are responsible for ensuring safety, improving clinical practice and maximizing patient flow in the new process (Baldassarre et al, 2018).…”
Section: Tqm 336mentioning
confidence: 99%